Functional endoscopic evaluation of swallowing findings in children with cerebral palsy - Barbosa, Sylvia Carolina Bruno (2012)
Objective: To analyse the findings of fiberoptic endoscopic evaluation of swallowing (FESS) in children with cerebral palsy (CP), discussing its importance for the process of speech therapy evaluation of oral pharyngeal dysphagia in this population. Method: It was a crosssectional and descriptive study, in which the FESS of nine children with CP of both sexes and mean chronological age of 3.4 ± 1.8 years were performed at the Interdisciplinary Dysphagia Ambulatory of Fortaleza University (UNIFOR), in the period of September to November, 2005. Results: The data showed the occurrence of precocious leakage of liquid to the hypopharynx before swallowing 7(77.77%); laryngeal penetration of liquid before the deglutition 4(44.44%); stasis post-swallowing of thick pasty 7(77.77%) and penetration after the deglutition of this consistence 5(55.55%). The main findings of FESS in children with PC involve precocious escape of food, delay at the beginning of deglutition, failure in oral control of liquids and greater difficulty in performing pharyngeal transit of thick pasty foods. Conclusion: In the evaluated patients, fiberoptic endoscopic evaluation of swallowing helped in the characterization of dysphagia manifestations in children with cerebral palsy. NCT: 00717028